Dinamika Pelatihan dan Gaya Hidup terhadap Peningkatan VO₂max: Pendekatan Kualitatif pada Atlet Tingkat Sekolah - Novia, Novia; Prastyawan, Riyani (Universitas Hamzanwadi, 2025)
This study aims to examine the dynamics of training and lifestyle in increasing VO₂max capacity in school-level athletes through a qualitative approach. The method used was a qualitative literature study by analyzing various relevant previous studies to gain an in-depth understanding of the factors influencing VO₂max increases. The results of the study indicate that high-intensity training methods such as High-Intensity Interval Training (HIIT) along with an active lifestyle that includes regular physical activity outside of formal training and a balanced nutritional pattern significantly contribute to increased aerobic capacity. Consistency and adherence to the training program also play a crucial role in the success of physiological adaptations. This study confirms that the combination of appropriate training and a healthy lifestyle results in a more effective increase in VO₂max than training alone without a good lifestyle support. In conclusion, integrative training programs and healthy lifestyle education need to be developed to support the sporting achievements and long-term health of young athletes in a sustainable manner. These findings can serve as a reference for coaches, educators, and policymakers in developing school-age sports